The Study of New Digital Adaptation In Marketing through Chatvertising And Their Impact On Young Consumers Mind - Meena, Krishan Kant (International Journal of Scientific Research and Management (IJSRM), 2015)
The study is based on new digital way to advertisement of product in age of digital marketing. New age, new market, new technology and new marketing change the way of organization business presentation. The significance of marketing strategies lead the new era of growth who contributions to the nation’s economic growth, the new business introduced some solutions to increase the practice of marketing. They efforts to encourage public and privet enterprise to adopt new modern app marketing as a tool to be take a competitive marketing in global marketing. This paper is concerned about the study of tool regarding modern marketing and promotion as social media marketing or app marketing through android or window phone chat applications. We called chatvertising (chat advertising) .chatvertising is a form of marketing or promotion which use chat application as a tool of communicating commercial or fund raising messages to an audience.in this paper ,there are a systematic review on its advantages and disadvantages.in addition the study also focus on the impact on young generation through chat applications on mobile phone.